2017
DOI: 10.1038/s41698-017-0042-x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of pharmacology, molecular pathology, and population data science to support precision gastrointestinal oncology

Abstract: Precision medicine has a goal of customizing disease prevention and treatment strategies. Under the precision medicine paradigm, each patient has unique pathologic processes resulting from cellular genomic, epigenomic, proteomic, and metabolomic alterations, which are influenced by pharmacological, environmental, microbial, dietary, and lifestyle factors. Hence, to realize the promise of precision medicine, multi-level research methods that can comprehensively analyze many of these variables are needed. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 107 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Last but not least, molecular pathological epidemiology (MPE) has emerged in recent years as a powerful approach in investigating relationship between exposures and disease risk. [29][30][31][32] Advances in cancer biology has clearly indicated that development of malignant disease is the result of a complicated interactions and integrations of genomic, epigenomic, proteomic and metabolomic alterations that involves environmental, microbial, dietary, pharmacological and lifestyle factors. In the era of precision oncology, treatment of an individual's cancer should be personalized according to the genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, molecular pathological epidemiology (MPE) has emerged in recent years as a powerful approach in investigating relationship between exposures and disease risk. [29][30][31][32] Advances in cancer biology has clearly indicated that development of malignant disease is the result of a complicated interactions and integrations of genomic, epigenomic, proteomic and metabolomic alterations that involves environmental, microbial, dietary, pharmacological and lifestyle factors. In the era of precision oncology, treatment of an individual's cancer should be personalized according to the genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our study has notable strengths including the use of a molecular pathological epidemiology database derived from two U.S. prospective cohort studies with long duration of follow-up. 53,54 Integrated data on tumor molecular characteristics and pathological findings allowed us to comprehensively characterize TIME subtypes of colorectal cancer. Of note, our study population was derived from a large number of cases from hospitals located throughout the U.S., contributing to increased generalizability of our findings.…”
Section: Time Subtypementioning
confidence: 99%
“…These are important studies in molecular pathological epidemiology that would shed light on future strategies in prevention and treatment of CRC. 31,32 There are several limitations in this study. Because of the limited amount of information available in this electronic medical record system, there is no clear definition of the disease staging, and hence, we were not sure whether the chemopreventive effects of aspirin were demonstrable in Stage I to III CRC.…”
Section: Discussionmentioning
confidence: 95%
“…In CRC, the potential benefit of aspirin with PIK3CA mutations, HPGD expression levels in normal colon, and the germline polymorphism that relates to beta‐catenin/WNT signaling pathway may also predict the efficacy of aspirin for cancer chemoprevention. These are important studies in molecular pathological epidemiology that would shed light on future strategies in prevention and treatment of CRC …”
Section: Discussionmentioning
confidence: 99%